Analisis Faktor-Faktor Yang Mempengaruhi Kesiapan Remaja Putri Dalam Menghadapi Menarche Pada Siswi Di Madrasah Ibtidaiyah (MI) Al-Khairiyah Pabean Kota Cilegon - Indah Nurfazriah (Jurnal Rumpun Ilmu Kesehatan, 2021)
A brief history Adolescence is a time of at this point of time, between childhood and adulthood, sexual maturity sets in and the reproductive organs (in women) begin to function (Menarche). The goal of this research was to better understand how to better prepare young women for menarche. Method: This study employs a quantitative Cross sectional research strategy. There were a total of 33 female students included in the sample. Multivariate analysis with the t test and bivariate analysis with the chi square test are employed. Results: The study found that a significant proportion of adolescents (25 out of 83.3%; p = 0.043) were unprepared for menarche because of a lack of knowledge, that a similar proportion (84.6%; p = 0.041) were severely anxious about entering puberty, and that a significant proportion (23 out of 88.5%; p = 0.009) had little support from their parents. Conclusion: It follows that adolescent girls' preparedness for menarche is significantly impacted by their prior exposure to information about the process, their degree of concern about it, and the level of support they receive from their parents.